Analysis comparing the recovery of airway reflexes and cognitive ability after sevoflurane with desflurane anesthesia - Mohammed Wajid Ali Khan; Prajnyananda Das; V Bhavani; Smit Thakkar; Sai Prannoy Nagella; Alok Dubey (Wolters Kluwer Medknow Publications, 2024)
Introduction: Although sevoflurane and desflurane have nearly identical blood-gas solubilities, current research suggests that airway reflexes recover more quickly with desflurane than sevoflurane; however, cognitive function recovery varies substantially. The current study was piloted to appraise the lengths of time needed to recover from anesthesia following desflurane and sevoflurane anesthesia. Materials and Methods: A prospective clinical trial was piloted among 70 adult non-obese subjects who underwent elective surgery and were classified I-II by the "American Association of Anesthesiologists (ASA)". Sevoflurane and desflurane were tested among the subjects who were equally distributed. These agents were used in accordance with a normal general anaesthesia procedure. After they were extubated, tests for regaining cognitive function and airway reflexes were carried out, and different time intervals were recorded. The observations were calculated and P < 0.05 was used to conduct the statistical analysis. Results: The average amount of time that passed between the patient's first vocal response and their first successful completion of the swallowing test was analogous between the two groups (T2) with 5.25 ± 3.11 vs 5.01 ± 2.12 in sevoflurane and desflurane, respectively. There was no significant variance at T2. For all the other time intervals of T1, T3, and T4, there was evidence of the significant variance.(P = 0.003; 0.0013; <0.001, respectively). Conclusion: Desflurane causes patients to recover more quickly than sevoflurane does after laparoscopic cholecystectomy under controlled circumstances.